PENGARUH PUPUK KANDANG DAN PUPUK ORGANIK LIMBAH BATANG PISANG TERHADAP PERTUMBUHAN UBI JALAR (Ipomoea batatas L.) - Susanti Indriya Wati; Wildan Shalihy (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Banana stem is still not optimally utilized by the communities that it causes as waste. One alternative solution is to process banana stem to be compost and liquid organic fertilizer, which is environmentally friendly to optimize plant growth and production. In this study, the compost and liquid organic fertilizer of banana stem applied on sweet potatoes. This study examines the compost and organic fertilizer of banana stem response on sweet potato (Ipomoea batatas L.). This research was conducted from October to December 2019 in the greenhouse of the Manokwari Agricultural Development Polytechnic. The research design used a one-factor Completely Randomized Block Design. The variables observed in the study were tendril length, root length, number of shoots, number of leaves, and fresh weight. The research data were analyzed using variance and Duncan's Multiple Distance Test (DMRT) at the 5% significance level. The results showed that the treatment of soil media + manure + liquid organic fertilizer of banana stems (1: 1: 1) gave the best result for the growth of tendril length (126.75 cm), root length (64.25 cm), number of leaves (56 fruits), the number of shoots (11 shoots), while the treatment of soil media + manure + banana stem compost with a ratio (1: 1: 1) impacted positively to wet weight (26.5 gr) of sweet potato.